Original researchThe delivery of prevention programmes for cardiovascular disease and chronic obstructive pulmonary disease in Lodz by primary care physicians - Godycki-Ćwirko, Maciej; Koziarska-Rosciszewska, Malgorzata; Kosiek, Katarzyna (Archives of Medical Science, 2010)
Introduction: In Poland, the National Health Fund (NHF) has contracted preventative interventions in primary health care (PHC) delivered by family physicians, internists, paediatricians and other physicians. The aim of the study was determining whether there is a correlation between PHC physicians’ specialisation and the rate of interventions delivered for the prevention of cardiovascular disease (CVD) and chronic obstructive pulmonary disease (COPD). Material and methods: A retrospective observational study of the NHF 2005 data related to the delivery of prevention programmes using Spearman’s rank correlation coefficient (rho). Results: Out of 133 PHC providers in Lodz, 25 participated in the cardiovascular disease (CVD) prevention programme, 22 in the chronic obstructive pulmonary disease (COPD) prevention programme at a basic level, and 20 at an extended level (with contract completion rates respectively of 55.2, 47.8 and 51.5%). When all three prevention programmes were analysed together, the correlation between the rate of preventative interventions by physicians with a particular specialisation and the contract completion rate was positive (rho > 0) only for family physicians. Conclusions: Participation of primary health care providers in preventative programmes and the rates of their delivery of interventions were low despite additional funding. The correlation between the proportion of physicians with a particular specialisation, involved in CVD and COPD prevention interventions delivery, and the rate of the programme accomplishment was the strongest for family physicians.